Basic instrumentation for informed decision-making in Nepal’s large irrigation systems: technical brief - Nepal, Santosh; KC, Jibesh; Khanal, A.; Neupane, N.; Bhatt, D. (International Water Management Institute, 2025)
The National Irrigation Policy of 2023 emphasizes the importance of volumetric water allocation for enhancing agricultural productivity in Nepal. A key part of this is enhancing the availability and use of flow data from canals to fields. Currently, Nepal lacks a consistent system for monitoring and managing irrigation water, resulting in inefficiencies and inequities in water distribution. Many systems suffer from poor infrastructure and ad hoc management, leading to serious head–tail disparities, where tail-end farmers receive little or no water, particularly in dry periods. The absence of regular flow and soil moisture data makes it difficult for both irrigation managers and farmers to make informed decisions about water allocation and irrigation scheduling. To support the policy’s goals, the International Water Management Institute (IWMI), in partnership with the Department of Water Resources and Irrigation (DWRI), initiated a pilot intervention in the Babai Irrigation Project in western Nepal. The project involves the installation of basic instruments that monitor real-time water flow, soil moisture, and weather conditions. These tools help irrigation managers to distribute water more efficiently. This approach is expected to reduce water-use conflicts, promote equity, and strengthen the role of Water User Associations in managing irrigation fairly and effectively.